The Effect of Total Views and Total Videos on Super Chat Earnings with Total Subscribers as Intervening Variable among Virtual YouTubers in Vietnam and Thailand - Mohammad, Wily; Maulidiyah, Nabilla Ryca (Indonesian Journal Publisher, 2023)
This quantitative research employs Partial Least Squares Structural Equation Modeling (PLS SEM) using Smart PLS 4 to analyze the financial dynamics of VTuber YouTube channels in the Vietnam and Thailand. The study utilized purposive sampling, comprising 77 channel samples, to explore the relationships between key variables. This research found that Total Subscribers has positive and significant effect to Super Chat Earnings, Total Views has negative and significant effect to Super Chat Earnings, Total Videos has negative but not significant effect to Super Chat Earnings, Total Videos has negative and significant effect to Super Chat Earnings through Total Subscribers, Total Views has negative and significant effect to Super Chat Earnings through Total Subscribers, Total Videos has negative and significant effect to Total Subscribers, and Total Views has negative and significant effect to Total Subscribers of Vietnam and Thailand VTuber YouTube channels